Contrast echocardiography facilitates appropriate management of hospitalized patients with coronavirus disease 2019 (COVID-19) and suspected right ventricular masses: case series. Issue 3 (10th March 2021) - Botrous, Christina; Bioh, Gabriel; Patel, Ashish; Hampson, Reinette; Senior, Roxy
Abstract: Background: Coronavirus disease 2019 (COVID-19) infection is associated with a coagulopathy with high incidence of venous thrombo-embolism. However, bleeding risk is also significant, causing difficulty in initiating and adjusting anticoagulation therapy in case of suspected thrombi. Cardiac masses can be challenging to be identified properly in the context of this disease. The use of bedside contrast echocardiography (CE) can be of a great value in this situation decreasing procedure-related risk and allowing proper diagnosis and management of a cardiac mass. Cases summary: We present two cases who were admitted with severe COVID-19 infection. Both cases had additional risk factors for hypercoagulability. Un-enhanced echocardiography was performed and revealed right ventricular (RV) dysfunction with a suspected RV mass. The use of bedside CE could confirm a RV thrombus in the first case and exclude it in the second case. Hence, anticoagulation therapy could be adjusted accordingly in both patients. Discussion: Coronavirus disease 2019 infection is associated with peripheral thrombo-embolism and cardiac thrombi. Given the critical condition of many patients affected by COVID-19, imaging for thrombo-embolic events is often restricted. With the use of bedside CE, cardiac masses may be correctly identified, aiding proper adjustment of anticoagulation therapy.